EFFECTS OF PHOSPHATE-SOLUBILIZING BACTERIA FROM PROBIOTIC AND PHOSPHORUS FERTILIZATION ON JUICE CHARACTERISTICS OF BROWN MIDRIB SORGHUM (Sorghum bicolor L. MOENCH) - Riesi Sriagtula; Mardhiyetti Mardhiyetti; Gusri Yanti; James Hellyward (BIOTROPIA, 2025)
HIGHLIGHTS- Bacillus sp. probiotics can replace 100% inorganic phosphate fertilizer.- Sorghum stem diameter strongly correlates with juice volume.- Juice yield was not affected by phosphorus dose or Bacillus sp. colony size.- Sorghum juice sugar content reached 11.77–12.75% Brix.- Phosphate-solubilizing bacteria improved phosphorus availability in ultisol. ABSTRACTThis study was conducted to observe the effects of phosphate-solubilizing bacteria (PSB) combined with different phosphorus fertilizer levels on the juice characteristics of the BMR sorghum mutant line. The research was carried out at the Edufarm of the Faculty of Animal Science, Andalas University, Padang, using a randomized block design (RBD) with four treatments and four replications. The treatments were as follows: P0 = Urea + KCl + 0% TSP + PSB; P1 = Urea + KCl + 50% TSP + PSB; P2 = Urea + KCl + 75% TSP + PSB; and P3 = Urea + KCl + 100% TSP (control). The PSB used was obtained from Waretha Probiotics, consisting of Bacillus sp. culture at a dose of 10 mL per planting hole, equivalent to 10⁷ cfu/g. The parameters measured were sugar content (%Brix), volume of stem juice (mL), and the correlation of various parameters with stem juice volume. The results showed that the application of probiotic Bacillus sp. and different dosages of phosphorus fertilizer did not result in significant differences for all parameters (P > 0.05). Sugar content and juice volume ranged from 11.78 to 12.75 (%Brix) and 188.75 to 218.5 (mL/stem), respectively. The correlation coefficient analysis indicated significant positive correlations between stem diameter (r = 0.575*) and fresh stem weight (r = 0.504*) with the volume of sorghum stem juice. It was concluded that the application of PSB from Bacillus sp. can replace phosphorus fertilizer, producing sugar content and juice yield comparable to the 100% P fertilizer treatment. A correlation was observed between stem diameter and fresh stem weight with stem juice volume. PSB was found to play a crucial role in increasing phosphate availability to plants. The implications of this research include the potential production of forage sorghum with high Brix content for ruminant energy and Water-Soluble Carbohydrates (WSC) for silage production.